Topological framework for directional amplification in driven-dissipative cavity arrays - Clara C. Wanjura (Nature Portfolio, 2020)
In information processing applications, directional amplifiers are key components which can be realized in very different systems. Here, the authors present a theoretical framework based on the introduction of a topological invariant that helps to understand directional amplification in coupled cavity arrays.